Relationship between consumption of MRSA-active antibiotics and burden of MRSA in acute care hospitals in Catalonia, Spain. (27th November 2014) - Grau, Santiago; Fondevilla, Esther; Freixas, Núria; Mojal, Sergi; Sopena, Nieves; Bella, Feliu; Gudiol, Francesc; ,; Balet, Antònia; Pérez, Rafel; Pons, Montserrat; García-Penche, Rosa; et al.
Abstract: Objectives: To analyse the possible relationship between consumption of old and new MRSA-active antibiotics and burden of MRSA in acute care hospitals in Catalonia during the period 2007–12. Methods: Fifty-four hospitals participating in the VINCat Programme were included. Proportion of MRSA (resistant isolates of Staphylococcus aureus per 100 isolates of S. aureus tested), incidence of new cases of infection [new cases of MRSA per 1000 occupied bed-days (OBD)] and incidence of cases of bacteraemia (MRSA bacteraemia cases per 1000 OBD) were determined to estimate the annual MRSA burden. Antibiotic consumption was calculated in DDD/100 OBD. Cost was expressed in euros/100 OBD. Results: MRSA rates remained stable over the study period, with the proportion of MRSA ranging from 20% to 22.82% in 2007 and 2012, respectively ( P  = 0.864). Consumption of old MRSA-active antibiotics (vancomycin and teicoplanin) did not change significantly, with values from 1.51 to 2.07 DDD/100 OBD ( P  = 0.693). Consumption of new MRSA-active antibiotics (linezolid and daptomycin) increased significantly, with values rising from 0.24 to 1.49 DDD/100 OBD ( P  < 0.001). Cost increased by almost 200%. Conclusions: A widespread and steady increase in consumption of new MRSA-active antibiotics was observed among acute care hospitals in Catalonia, in spite of a stable MRSA burden. At the same time, consumption of old drugs remained stable. Such trends resulted in a significant increase in cost. Our findings suggest that factors other than the proportion of methicillin resistance among S. aureus may influence the use of old and new MRSA-active antibiotics in the clinical setting.